High-Dose Methylprednisolone to Prevent Platelet Decline in Preeclampsia: A Randomized Controlled Trial. Issue 1 (July 2016) - Pourrat, Olivier; Dorey, Marie; Ragot, Stéphanie; de Hauteclocque, Astrid; Deruelle, Philippe; Dreyfus, Michel; Pierre, Fabrice
Abstract : OBJECTIVE: To evaluate whether early administration of high-dose methylprednisolone limits the fall of platelets in preeclampsia. METHODS: A randomized trial of 180 mg methylprednisolone or placebo administered in divided doses over 36 hours was conducted in women admitted for preeclampsia and platelet counts below 150×10 9 /L in four French academic centers. Patients were not included when platelet counts were below 50×10 9 /L or when immediate delivery was required. The primary study outcome was the proportion of patients with platelet counts above 100×10 9 /L 36 hours after the first dose of study medication. The total sample size needed to detect a 23% difference in the rate of this outcome between groups with a one-tailed α of 0.05 and 90% power was 94 patients. RESULTS: Thirty-six patients were randomly assigned to receive methylprednisolone and 34 placebo between October 2007 and May 2011. Platelet counts above 100×10 9 /L at 36 hours after the first dose of study medication were recorded in 30 (83%) in the active group and 29 (85%) in the placebo group (relative risk 0.98, 95% confidence interval 0.80–1.20; P =.82). The only adverse potentially study-related event was hyperglycemia in one woman allocated to methylprednisolone. CONCLUSION: In women with preeclampsia and platelet counts under 150×10 9 /L, methylprednisolone was not effective in maintaining platelet counts above 100×10 9 /L. CLINICAL TRIAL REGISTRATION: EU Clinical Trials Register, http://clinicaltrialsregister.eu, EudraCT 2006-004881-15-FR. Abstract : Supplemental Digital Content is Available in the Text.In women with preeclampsia and platelet counts under 150×10 9 /L, methylprednisolone was not effective in maintaining platelet counts above 100×10 9 /L.